“There Is No Safe Place in This Plant”: Refugee Workers in Canadian Meatpacking and the Limits of Permanent Legal Status - Bragg, Bronwyn; Hyndman, Jennifer (Refuge: Canada's Journal on Refugees, 2024)
Following spring 2020’s deadly COVID-19 outbreaks in the Alberta meatpacking industry, we conducted research with meatpackers who were formerly resettled refugees and now Canadian permanent residents (PRs) or Canadian citizens. Research with temporary foreign workers often promotes permanent legal status as a solution to poor conditions of precarious work in Canada, but even with permanent immigration status, former refugees experienced a large gap between their rights as “guaranteed” by the state through their PR status and their daily work in meatpacking plants in rural Alberta. Work in the plants is dangerous, dirty, and difficult, and employees found it difficult to enact their rights as workers. Access to adequate breaks, sick days, and other mandated requirements was reported to be contested and contingent. Former refugees working in this sector experience unexpected “unfreedom.”